1999
DOI: 10.1109/83.760338
|View full text |Cite
|
Sign up to set email alerts
|

A wavelet visible difference predictor

Abstract: Abstract-In this paper, we describe a model of the human visual system (HVS) based on the wavelet transform. This model is largely based on a previously proposed model, but has a number of modifications that make it more amenable to potential integration into a wavelet based image compression scheme. These modifications include the use of a separable wavelet transform instead of the cortex transform, the application of a wavelet contrast sensitivity function (CSF), and a simplified definition of subband contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
68
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 131 publications
(71 citation statements)
references
References 44 publications
(101 reference statements)
0
68
0
2
Order By: Relevance
“…It has been shown in (Bradley, 1999;Nadenau et al, 2003) that the performance of image compression techniques can be significantly improved by exploiting the limitations of the HVS for compression purposes. To achieve this aim, the HVS-model can be embedded in the compression algorithm to optimise the perceived visual quality.…”
Section: Characteristics Of the Human Visual Systemmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been shown in (Bradley, 1999;Nadenau et al, 2003) that the performance of image compression techniques can be significantly improved by exploiting the limitations of the HVS for compression purposes. To achieve this aim, the HVS-model can be embedded in the compression algorithm to optimise the perceived visual quality.…”
Section: Characteristics Of the Human Visual Systemmentioning
confidence: 99%
“…Research has shown that embedding the Human Visual System (HVS) model into compression algorithms yields significant improvement in the visual quality of the reconstructed images (Aili et al, 2006;Antonini et al, 1992;Bradley, 1999;HSontsch & Karam, 2000;Nadenau et al, 2003;Sheikh Akbari & Soraghan, 2003;Thornton et al, 2002;Voukelatos & Soraghan, 1997). It has been shown in (Bradley, 1999;Nadenau et al, 2003) that the performance of image compression techniques can be significantly improved by exploiting the limitations of the HVS for compression purposes.…”
Section: Characteristics Of the Human Visual Systemmentioning
confidence: 99%
See 3 more Smart Citations